2021
DOI: 10.1021/acsbiomaterials.1c00745
|View full text |Cite
|
Sign up to set email alerts
|

RGDSP-Decorated Hyaluronate Hydrogels Facilitate Rapid 3D Expansion of Amylase-Expressing Salivary Gland Progenitor Cells

Abstract: In vitro engineering of salivary glands relies on the availability of synthetic matrices presenting essential cell-instructive signals to guide tissue growth. Here, we describe a biomimetic, hyaluronic acid (HA)-based hydrogel platform containing covalently immobilized bioactive peptides derived from perlecan domain IV (TWSKV), laminin-111 (YIGSR, IKVAV), and fibronectin (RGDSP). The HA network was established by the thiol/acrylate reaction, and bioactive peptides were conjugated to the network with high effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(41 citation statements)
references
References 55 publications
(114 reference statements)
0
41
0
Order By: Relevance
“…From ECM Components in Repair Biology: In Vitro Engineering of Salivary Glands Using Perlecan Domain IV, Laminin-111 and Fibronectin Peptide Scaffolds Peptides derived from perlecan domain IV (TWSKV), laminin-111 (YIGSR, IKVAV), and fibronectin (RGDSP) have been incorporated into HA scaffolds with RGDSP and TWSKV peptide HA scaffolds significantly accelerating cell proliferation (Fowler et al, 2021). Perlecan peptide TWSKV triggers differentiation of salivary gland cells into self-assembling acinilike structures expressing salivary gland biomarkers that secrete α-amylase (Pradhan et al, 2009;Pradhan et al, 2010).…”
Section: Application Of Stimulatory Peptides Derivedmentioning
confidence: 99%
See 1 more Smart Citation
“…From ECM Components in Repair Biology: In Vitro Engineering of Salivary Glands Using Perlecan Domain IV, Laminin-111 and Fibronectin Peptide Scaffolds Peptides derived from perlecan domain IV (TWSKV), laminin-111 (YIGSR, IKVAV), and fibronectin (RGDSP) have been incorporated into HA scaffolds with RGDSP and TWSKV peptide HA scaffolds significantly accelerating cell proliferation (Fowler et al, 2021). Perlecan peptide TWSKV triggers differentiation of salivary gland cells into self-assembling acinilike structures expressing salivary gland biomarkers that secrete α-amylase (Pradhan et al, 2009;Pradhan et al, 2010).…”
Section: Application Of Stimulatory Peptides Derivedmentioning
confidence: 99%
“…Laminin-111 peptide-HA hydrogels have also been shown to act as a synthetic basement membrane (Yamada et al, 2013). Conjugation of RGDSP peptide to HA gels improves cell viability, accelerates formation of epithelial spheroids, and promotes the expansion of 3D progenitor cell populations, representing the first step toward the development of an engineered salivary gland (Fowler et al, 2021). Primary salivary human progenitor stem cells undergo acinar-like differentiation in HA hydrogel cultures and incorporation of basement membrane peptides derived from perlecan and laminin-111 further directs the development of 3D salivary gland-like spheroids (Srinivasan et al, 2017).…”
Section: Application Of Stimulatory Peptides Derivedmentioning
confidence: 99%
“…Hydrogel precursors, including thiolated (HA-SH) and acrylated HA (HA-AES), as well as maleimide-functionalized RGDSP peptide (MI-RGDSP), were prepared as previously reported 47 . Cellular constructs were produced by dispersing hS/PCs in a solution containing HA-SH or HA-SH/MI-RGDSP before adding the HA-AES solution, resulting in HA or RGDSP cultures, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…We have also developed hyaluronic acid (HA)-based hydrogels that support the 3D culture of hS/PCs under defined conditions and identified a mechanical stiffness regime that promotes the development of multicellular spheroids 46 . Recently, we demonstrated that HA matrices with a covalently immobilized RGDSP peptide, a fibronectin-derived integrin-binding ligand, promoted the rapid 3D expansion of amylase-expressing hS/PCs 47 . However, the expression of K7 as the 3D cultures expand remains unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…One possible explanation is that L 1p -FH could have activated resident hS/PCs that contributed to gland homeostasis through interactions with specific integrins. Likewise, a fibronectin (RGDSP)-modified HA hydrogel also improved cell viability, accelerated epithelial spheroids formation and promoted the progenitor cell population expansion 225 . Peptide-modified hydrogels probably promote the proliferation and differentiation of salivary gland stem cells by regulating the growth microenvironment of salivary gland stem cells.…”
Section: Biomaterials Science Accepted Manuscriptmentioning
confidence: 99%